Breaking taboos! From silence to support: understanding children’s sexuality in early childhood pedagogical practice - Lehn, Elisabeth Walsøe; Chahboun, Sobh (Frontiers in Education, 2025)
Sexual education has been a subject of scholarly focus for over three decades, yet addressing sexuality as an integral aspect of human development remains a persistent challenge. In early childhood education, the topic is often stigmatized, leaving educators without the tools or confidence to approach it constructively. Recognizing sexuality as a natural and developmental process is essential for fostering respect, healthy relationships, and personal growth in children. This article explores kindergarten teachers’ practices and perceptions concerning children’s sexuality, examining societal taboos and the critical gaps in teacher education. By integrating insights from policy documents and empirical research, this study underscores the necessity of incorporating comprehensive sexuality education into teacher training programs. It advocates for a shift from silence to proactive engagement, empowering educators to address children’s natural expressions with empathy and respect.